Sonographic demonstration of human small intestinal migrating motor complex phase III. Issue 2 (17th October 2012) - Liu, C. J.; Huang, S. C.; Huang, Y. C.; Liu, C. Y.; Chen, H. I.
Abstract Background Migrating motor complex phase III (MMC phase III) of intestine is an important physiological mechanism traditionally recognized by myoelectric recordings or pressure tracings. Direct imaging is difficult and sonographic visualization in human has not been reported. Methods We have demonstrated this unique phenomenon in three patients who underwent abdominal sonographic examinations. Characteristic images were recorded by videotape and both spatial and temporal features were analyzed. Key Results Occurrences of multiple equally spaced, rhythmic intestinal contractions were observed. Parameters including wave frequency, propagation velocity, and duration of the events agreed with those of the well‐known phase III. The presence of distinct cyclic patterns observed in two and abolition by meal in the other patient further support our conclusion. Conclusions & Inferences We conclude that the migrating waves observed in our study represent the human MMC phase III. This unique finding in human subjects merits further investigation.